Axillary Dissection and Nodal Irradiation Can Be Avoided for Most Node-positive Z0011-eligible Breast Cancers: A Prospective Validation Study of 793 Patients. Issue 3 (September 2017) - Morrow, Monica; Van Zee, Kimberly J.; Patil, Sujata; Petruolo, Oriana; Mamtani, Anita; Barrio, Andrea V.; Capko, Deborah; El-Tamer, Mahmoud; Gemignani, Mary L.; Heerdt, Alexandra S.; Kirstein, Laurie; Pilewskie, Melissa; et al.
Abstract : Objective: To determine rates of axillary dissection (ALND) and nodal recurrence in patients eligible for ACOSOG Z0011. Background: Z0011 demonstrated that patients with cT1-2N0 breast cancers and 1 to 2 involved sentinel lymph nodes (SLNs) having breast-conserving therapy had no difference in locoregional recurrence or survival after SLN biopsy alone or ALND. The generalizability of the results and importance of nodal radiotherapy (RT) is unclear. Methods: Patients eligible for Z0011 had SLN biopsy alone. Prospectively defined indications for ALND were metastases in ≥3 SLNs or gross extracapsular extension. Axillary imaging was not routine. SLN and ALND groups and radiation fields were compared with chi-square and t tests. Cumulative incidence of recurrences was estimated with competing risk analysis. Results: From August 2010 to December 2016, 793 patients met Z0011 eligibility criteria and had SLN metastases. Among them, 130 (16%) had ALND; ALND did not vary based on age, estrogen receptor, progesterone receptor, or HER2 status. Five-year event-free survival after SLN alone was 93% with no isolated axillary recurrences. Cumulative 5-year rates of breast + nodal and nodal + distant recurrence were each 0.7%. In 484 SLN-only patients with known RT fields (103 prone, 280 supine tangent, 101 breast + nodes) and follow-up ≥12 months, the 5-year cumulative nodal recurrence rate was 1% and did not differ significantly by RT fields. Conclusions: We confirm that even without preoperative axillary imaging or routine use of nodal RT, ALND can be avoided in a large majority of Z0011-eligible patients with excellent regional control. This approach has the potential to spare substantial numbers of women the morbidity of ALND.